PERLUASAN TERITORI RUMAH DI PERUMAHAN RELOKASI NELAYAN KECAMATAN AMPENAN - Widyani Utami Dewi, Tjok Istri; Widya Paramadhyaksa, I Nyoman; Sueca, Ngakan Putu (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 1 (2016): April 2016DO - 10.24843/JRS.2016.v03.i01.p02, 2016)
Abstract This is a study of new settlements that accommodate communities which have been relocated due to natural disasters. Case studies are carried out in the fishing communities of Ampenan and Tanjung Karang coasts of Lombok which were hit by tidal wave disasters in 1997. In order to house the affected communities, the government of Mataram City developed housing units which have since been gradually adapted by dwellers to meet their needs for extra space. These forms of adaptation include: (1) introduction of new functions; (2) the use of public spaces for private purposes; (3) the inclusion of space outside domestic territory for personal use; (4) development of additional fencing; and (5) an expansion of house floor areas. These also in turn bring about change in the occupational profile of inhabitants. The main aim of this study is to identify factors underlining the aforementioned conditions. It implements qualitative research methods derived from the paradigm of phenomenology. Data collection was centralized at Kampong Gatep - a settlement of Ampenan Coast -, where 19 housing units to be studied are located. These 19 family homes exist among the total of 56 relocated family groups. Since each unit is limited in scale, its occupants began their spatial expansion by containing their belongings within their spatial allocation. This gradually expanded as their needs changed. The final findings shows that the dominant factors behind such spatial expansion include: (1) inhabitants' past habit to use space outside domestic sphere; (2) increasing demands for space due to changes in lifestyle; (3) limited space provided by local government for each unit; (4) space available outside housing unit; and (5) locally derived consensus in regard to non-domestic space utilization. Keywords: territoriality, relocated settlement, fishing community, Ampenan Abstrak Pemerintah Daerah Kota Mataram memberi bantuan berupa perumahan relokasi kepada nelayan korban bencana gelombang pasang yang terjadi di sepanjang pantai Ampenan dan Tanjung Karang yang telah terjadi sejak tahun 1997. Pascarelokasi, banyak fenomena terkait teritori yang terjadi di perumahan relokasi berupa: (1) penambahan fungsi bangunan; (2) pemanfaatan ruang publik untuk keperluan pribadi; (3) pemanfaatan lahan sisa; (4) penambahan pagar rumah; (5) penambahan luas lantai; dan (6) perubahan profesi kepala keluarga. Mencermati gambaran fenomena tersebut, muncullah gagasan untuk memfokuskan arah penelitian kearah teritorialitas. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang melatarbelakangi adanya perluasan area teritori. Metode penelitian yang digunakan adalah metode kualitatif dengan paradigma fenomenologi. Lokasi penelitian ini adalah di Kecamatan Ampenan, tepatnya di perkampungan Gatep. Jumlah masyarakat nelayan pesisir Pantai yang telah direlokasi pada tahap pertama adalah 56 kepala keluarga. Kasus dipilih menggunakan teknik purposive (bertujuan), yaitu dengan  memilih 19 kasus yang memiliki karakter kuat sesuai dengan fenomena yang terjadi. Fenomena-fenomena yang terkait perluasan area teritori bermula dari terbatasnya fasilitas yang disediakan Pemerintah Daerah di perumahan relokasi. Terbatasnya ruang menyebabkan penghuni mulai melakukan invasi dengan meletakkan property pribadi di lahan-lahan sisa yang tersedia. Hasil akhir penelitian ini menunjukkan bahwa terdapat beberapa faktor dominan yang menjadi latar belakang adanya perluasan area teritori, antara lain: (1) masa lalu; (2) tuntutan kebutuhan ruang; (3) keterbatasan lahan; (4) adanya lahan sisa; dan (5) konsensus penggunaan lahan. Kata kunci: teritorialitas, perumahan relokasi, nelayan, Ampenan.
Keywords: teritorialitas, perumahan relokasi, nelayan, Ampenan